CLINICAL CHARACTERISTICS AND DISEASE COURSE BEFORE AND AFTER SARS-COV-2 INFECTION IN A LARGE COHORT OF SYSTEMIC SCLEROSIS PATIENTS - Guler, A. Avanoglu; Ozcimen, B.; Aydogdu, M.; Sari, A.; Aliyeva, N.; Tuzun, N.; Tufan, A. (Bmj Publishing Group, 2023)
[Abstract Not Available]
European Congress of Rheumatology (EULAR) -- MAY 31-JUN 03, 2023 -- Milan, ITALY
Keywords: COVID; Lungs; Systemic sclerosis